Upaya Penanaman Jiwa Entrepreneurship melalui Kegiatan Market Day di SD Islam Nurul Izzah Kota Malang - Silmi Farichah; Munirul Abidin (MANAZHIM, 2023)
Not everyone has an entrepreneurial spirit, but it can be cultivated through various means. Many institutions strive to find solutions for instilling an entrepreneurial mindset in students, one of which is Nurul Izzah Islamic Elementary School in Malang City. This research method is qualitative, employing a case study approach, in which the researcher will delve deeper into information regarding the school's efforts to instill entrepreneurship in students through Market Day activities at Nurul Izzah Islamic Elementary School in Malang City. The objectives of this study are as follows: 1) To explain the efforts in instilling an entrepreneurial spirit. 2) To understand the cultivation of an entrepreneurial spirit through Market Day. 3) To analyze the efforts in instilling an entrepreneurial spirit through Market Day at Nurul Izzah Islamic Elementary School in Malang City. The findings of the research are as follows: 1) The cultivation of an entrepreneurial spirit can be achieved through training and education. 2) The cultivation of an entrepreneurial spirit through Market Day involves teachers, students, and parents, with the aim of developing marketing skills. 3) The cultivation of an entrepreneurial spirit through Market Day at Nurul Izzah Islamic Elementary School in Malang City is implemented through three stages: the production stage, providing information to parents and the entire school community as stakeholders, and the marketing stage. However, the implementation is not entirely supported, as there are both internal and external inhibiting factors.